Rumor its legal and Sharia provisions - Hilal Al-Miyahi, Researcher. Saad; Fahimi, Prof. Dr. Aziz Allah (Basra studies journal, 2024)
Observing the various crises humanity is facing today across societies and individuals emphasizes an important reality: much of these crises stem from significant moral gaps, negatively affecting both the spiritual and behavioral aspects of contemporary humans. Islamic societies have had their share of these multifaceted crises, significantly impacting the noticeable moral decline, especially considering the complexity characterizing present challenges. The contemporary situation bears significant changes, an unprecedented openness to diverse ideas, cultures, and behavioral patterns amidst the information revolution and the remarkable diversity in media and communication channels. In this article, we briefly discussed the topic of rumors, dividing the article into three chapters: Chapter One: We discussed rumors linguistically and terminologically. In Chapter Two: We pointed out the reasons for rumors, their types, and mentioned methods of their dissemination. As for Chapter Three: We discussed the impact of rumors on society, then mentioned ways to address them, concluding the article by citing research sources and providing an index of the research contents.